Pemanfaatan Media Sosial Sebagai Media Promosi Dalam Pemasaran Produk Tahu Pak Sugeng - Hidayah, Nenden Restu; Safitri, Latipah Nurma (Jurnal Dehasen Mengabdi, 2023)
Marketing is the process of marketing a finished product to the consumer. The current marketing system that is becoming a new trend is the online marketing system. By using online marketing, it will be easier and can be done anywhere in marketing a product using social media. Social media that is often used today is Facebook, Instagram and also TikTok, we as business people must also take advantage of these various social media in order to determine strategic planning for the company. Social media can also be used as a promotional medium to introduce products to the wider community. Marketing through social media has great advantages, one of which is the relatively cheaper cost compared to other media in carrying out promotional activities at the tofu factory in hamlet 03 sungsi hitam bengkulu tengah. As we know that white tofu is one of the staple food companions of the community.